Inclusive education and training systems: Illusion or reality? The story of Nothemba. - Lebusa A. Monyooe (Arizona State University, 2005)
This article explores the challenges facing the South African National Department of Education in its commitment to provide equal educational opportunities for all. The Story of Nothemba is central to the theme of this paper. It describes the story of a South African girl born in eQebe, whose physical disability and systematic disregard for her constitutional rights dashed her life time dream and passion to become a lawyer in a democratic South Africa. The paper argues for a critical interrogation of the following dynamics that have the potential to complicate both the implementation and optimization of the Inclusive Education Policy: (i) Understanding the social stereotypes about disability, (ii) Teacher empowerment, (iii) Systemic imbalance between support and expectations, (iv) Adopting relevant curriculum policy and assessment strategies and practices, and (v) Utilizing the research logic to inform policy implementation. The paper further calls for a robust interrogation at conceptual level about disability' to inform the current policies on education and training, teacher training and development, curriculum and assessment strategies.